A simple and efficient multi-residue method based on quechers for pesticides determination in palm oil by liquid chromatography time-of-flight mass spectrometry - Sobhanzadeh, E.; Bakar, N.K.A.; Abas, M.R.; Nemati, K. (2012)
In this study, a rapid, specific and sensitive multi-residue method based on acetonitrile extraction followed by dispersive solid-phase extraction (d-SPE) clean-up was implemented and validated for multiclass pesticide residues determination in palm oil for the first time. Liquid-liquid extraction followed by low-temperature precipitation procedure was evaluated in order to study the freezing-out clean-up efficiency to obtain high recovery yield and low coextract fat residue in the final extract. For clean-up step, d-SPE was carried out using a combination of anhydrous magnesium sulphate (MgSO4), primary secondary amine, octadecyl (C18) and graphitized carbon black. Recovery study was performed at two concentration levels (10 and 100 ng g -1), yielding recovery rates between 74.52 and 97.1 with relative standard deviation values below 10 (n=6) except diuron. Detection and quantification limits were lower than 5 and 9 ng g -1, respectively. In addition, soft matrix effects (â¤Â±20) were observed for most of the studied pesticides except malathion that indicated medium (20-50) matrix effects. The proposed method was successfully applied to the analysis of suspected palm oil samples.